Supported ionic liquids as efficient strategies to reduce environmental contamination by cytostatic drugs - Francisco, R. (2021)
Cytostatic drugs are one of the most used therapeutic options to treat cancer. Considering that cancer prevalence is increasing at a fast rate, the consumption of these drugs is expected to increase in the future. Upon administration, cytostatics are mainly excreted trough urine. This urinary excretion is responsible for the contamination of sewage, wastewater treatment plants (WWTPs) effluents, and ultimately of the aquatic environment. Consequently, cytostatic drugs were already detected in estuaries, rivers, lakes and even in drinking water. Given the high toxicity of these drugs and the inefficacy of the current technologies for their removal, disruptive technologies are necessary in order to mitigate this serious environmental and public health problem. In this line, we aim to remove these drugs before they reach the water cycle, i.e., directly from the contamination source (urine). In order to achieve this goal, Supported Ionic liquids (SILs) are here investigated since they combine the advantages of solid supports and the tunable characteristics of ILs. Several SILs using silica as the support material have been prepared and chemically and morphologically characterized. The SILs adsorption capacity for distinct cytostatic drugs, namely cyclophosphamide (CP), mycophenoloate mofetil (MMF) and mycophenolic acid (MPA) was evaluated by determining adsorption kinetics and isotherms. Overall, the ILs’ cation structure plays the most relevant role in the removal efficiency of cytostatics from aqueous samples and urine, with the developed materials showing a significantly higher performance than non-modified silica and activated carbon.